2002
DOI: 10.1253/circj.66.779
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Arteriovenous Fistula Presenting as Chronic Pericardial Effusion.

Abstract: oronary arteriovenous fistula (CAVF) is an abnormal communication between a coronary artery and a cardiac chamber, great vessel, or other vascular structure. Most of them are found incidentally during coronary angiography (CAG), and are identified as a cause of a continuous murmur, myocardial ischemia, congestive heart failure or, rarely, bacterial endocarditis. [1][2][3] However, cases with pericardial effusion (PE) caused by rupture of the aneurysmal coronary artery are quite rare; only 3 cases of cardiac ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 9 publications
0
18
0
1
Order By: Relevance
“…Myocardial ischemia/infarction can occur from decreased coronary blood flow distal to the fistula and has been documented in patients with coronary fistulas with no evidence of coronary atherosclerosis. Rarely, pericardial effusion and sudden death can be a presenting feature [3,24]. In coronary artery fistulas the continuous murmur tends to be crescendo decrescendo in both systole and diastole, but louder in diastole.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Myocardial ischemia/infarction can occur from decreased coronary blood flow distal to the fistula and has been documented in patients with coronary fistulas with no evidence of coronary atherosclerosis. Rarely, pericardial effusion and sudden death can be a presenting feature [3,24]. In coronary artery fistulas the continuous murmur tends to be crescendo decrescendo in both systole and diastole, but louder in diastole.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Furthermore, they may have a valvular source or may originate from an atrial or ventricular arrhythmic substrate. Such complications may include myocardial infarction (MI) (4%)[136,137], congestive heart failure (20%)[136], infective endocarditis (reported in 4%-12% in different series)[81,136], atrial[138] and ventricular[139] arrhythmias, aneurysm (reported in 20% of cases)[96,140], rarely ruptured aneurysm with hemopericardium[141] and unruptured aneurysm[139,142], pericardial effusion[143], syncope[142,144] and sudden death[145]. It has been postulated that fistula-related complications increase with age[136].…”
Section: Discussionmentioning
confidence: 99%
“…Of resected aneurysmal wall of the fistula contained both arterial and venous elements. No thrombus or atherosclerosis [22]. One resected fistula segment revealed an artery with mural thinning, fresh thrombus and atherosclerosis [23] One report showed multiple thin-walled vessels ranging in size from 10-500 um found 5 mm beneath the endocardium and communicated directly with the LV lumen [10].…”
Section: Discussionmentioning
confidence: 99%